Cervical Motor and Nociceptive Dysfunction After an Acute Whiplash Injury and the Association With Long-Term Non-Recovery: Revisiting a One-Year Prospective Cohort With Ankle Injured Controls - Kasch, Helge; Carstensen, Tina; Ravn, Sophie Lykkegaard; Andersen, Tonny Elmose; Frostholm, Lisbeth (Frontiers in Pain Research, 2022)
Aims: To explore the development of cervical motor and nociceptive dysfunction in whiplash patients (WPs) and non-recovery based on injury-related work-disability 1-year after injury compared with ankle-injured controls (ACs). Methods: A 1-year observational prospective study examining consecutive WPs, and age- and sex-matched ACs at 1 week and 3, 6 months and 1-year post-injury using semi-structured interviews; global pain rating (VAS0-10) and from McGill Pain Questionnaire the pain rating index (PRI-T), number-of-words-chosen; examining nociceptive functioning using cold pressor test (CPT), pressure algometry, and methodic palpation, and central pain processing using counter-stimulation; examining motor functioning by active cervical range-of-motion (CROM), neck strength (maximal voluntary contraction flexion/extension (MVC). One-year work disability/non-recovery was determined using a semi-structured interview. Results: A total of 141 WPs and 40 ACs were included. Total pain rating index (PRI-T) and number-of-words chosen (NWC) were higher in ACs initially, however, higher in WPs after 3, 6 months, and 1 year. Ongoing global pain was higher in WP initially and after 3, 6 months, but not 1 year. Pressure pain thresholds were reduced, and palpation were higher in the neck and jaw in WPs after 1 week, but not consistently different from AC afterwards. Cervical mobility was reduced in WPs after 1 week, 3, 6 months, but not 1 year and MVC was significantly reduced in WPs as compared with ACs after 1 week, and 1-year, but not 3, and 6 months. One-year non-recovery was only encountered in 11 WPs, and not in the AC group. Non-recovered WPs (N-WP) had consistently significantly higher VAS0-10, PRI-T, NWC, and reduced pressure pain thresholds and raised muscle-tenderness and reduced active-cervical-range of-motion, reduced active-neck-flexion/extension, and reported higher neck disability scores than recovered WPs. Of special interest there was increasing tenderness in trigeminal derived muscles based on palpation scores and marked reduction of PPDT most pronounced in N-WP as compared to recovered WPs and ACs. Conclusion: Cervical motor dysfunction and segmental nociceptive sensitization were present from early after injury in WPs and prolonged in N-WPs. Difference in trigeminal and cervical motor and sensory function in N-WPs could be of interest for future treatment studies.